Determinants of Share Prices of Agriculture Listed Firms - Abel, Sanderson; Henry, Muleya; Mokumako, Tebogo; Mukarati, Julius; Le Roux, Pierre (International Journal of Economics and Financial Issues, 2024)
The stock market plays an important role in economic development by promoting capital formation and enhancing economic growth. The stock market is among the main sources of financing in the critical sector of the economy. Trading of securities on the Zimbabwe stock exchange facilitates savers and users of capital by fund pooling, risk sharing and transferring wealth. One of the important sectors of the Zimbabwean economy devoid of adequate financing is the agricultural sector. This sector has been experiencing several challenges over the period 2002 -2022 mostly from lack of sustainable finance especially from private investment. It is assumed that lack of funding is due to volatility of stock prices. The objective of the study is to analyze different factors affecting share price of agriculture sector listed firm on the Zimbabwe Stock Exchange using the panel regression model. Based on the random effect the study established that share prices are determined by earnings per share, price earnings ratio and return on equity positively impacts stock prices in Zimbabwe. The government should control inflation to ensure price stability to aid in easy financial planning. Further the governments should promote agricultural growth initiatives and strategies which would stimulate demand for agricultural oriented stocks.